A new species of Melanagromyza Hendel (Diptero: Agromyzidae), pest of the tomato fiower bud in Colombia - SANABRIA DE ARÉVALO, ISABEL; ZENNER DE POLANÍA, INGEBORG (Revista Colombiana de Entomología, 1994)
This research offers to the Colombian and world entomological community the identification of a species of the genus Melanagromyza Hendel (Diptera: Agromizidae), unknown to science, in spite of attacking a plant of economic importance as the tomato. The additional information about its ecology and life habits provided are basic for further studies of management, interrelationship with the host plant, and cytogenetics, among others. For the study, sufficient material of eggs, larvae, pupae, and adults, as well as flower buds, was available. The ínvestigation was carried out at the entomological laboratories of the Instituto de Ciencias Naturales, UN in Santafé de Bogotá and CI «Tibaitatá» of ICA in Mosquera (Cund.), during 1993, using microscopes with incorporated micrometers, to observe the relevant morphological characteristics of the life stages of the insect. The result is the description and nomination of Melanagromyza socolena and the presentation of data on external morphology of the adult, the male genitalia; the egg, larva, and pupa. Illustrations and other data concerning the different developmental stages of the species are included.